Comparison of salinity tolerance between Avicenna marina and Rhizophora mucronata Karachi coast, Pakistan - Maria Ashraf; Fuad Muhammad; Jafron Wasiq Hidayat; Muhammad Ayyaz; Waqar Ahmed; Muhammad Sohail Anwar; Kamil Ahmed; Muhammad Yaseen (BIORE Scientia Publisher, 2023)
Mangrove propagule size variation is an important factor in their survival. The main aim of this study was to determine the productivity and identify the comparison between Avicenna marina and Rhizophora mucronata. However, it is less studied about the comparison of mangrove species and their salt tolerance in terms of seedling establishment of propagules. We investigated the propagules size variation of Avicennia marina and Rhizophora mucronata from the Indus delta and were grown in the polythene bags of 5x10″ filled with silty soil from field nursery. We used salinity and nutrients treatments to propagules to identify the growth rate of mangrove species. The surveying technique was also used to collect the information of mangrove forest from local communities. We detected that Rhizophora mucronata had a higher productivity rate due to the given concentration of 50% sea water. While the Avicennia marina showed a lower decline ratios growth at 25% salinity level with further increases in salinity. Using diffusion porometers and infrared gas analyzers (IRGAs), we revealed that stomatal conductance was higher in Rhizophora mucronata, followed by Avicennia marina. Moreover, our outcomes showed a higher Sodium and chloride ions with the increase in salinity and also demonstrated a higher accumulation in Avicennia marina. Overall, its was found that Avicennia marina is the most salt resistant species and it’s a dominated species in littoral forest. Our outcomes can help us to better understand the green infrastructure design of mangroves, suggesting that selecting multiple techniques ensure many post-tsunami restoration initiatives are encountering problems.